PENGARUH PEMBERIAN PUPUK ORGANIK HERBAFARM DAN BEBERAPA MEDIA TUMBUH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapaL.) DENGAN SISTEM BUDIDAYA HIDROPONIK NFT - Muhammad Zuhri; Islan Islan; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Pakcoy (Brassica rapa L) is member of Brassicaceae family. With hight nutritional content pakcoy consumptions in Indonesian society increase every year, but it is still far from the recommended level of the consumption. This research aims to determine the effect of the interaction and single concentration of Herbafarm, growing media, and to obtain the dosage of Herbafarm fertilizer and the best growing medium for the production of pakcoy with NFT hydroponic system. This research has been conducted in Green House Hydroponic at Jl. Tulip Sukajadi, Pekanbaru. This research used split plot design. The first factor was Herbafam fertilizer (H) as a subplot with concentration of Herbafarm 0, 15, 20, and 25 ml.l-1 of water. The second factor are various growing media (M) as the main plot as the growth medium, they arerockwool, cocopeat, and charcoal husk. The result of the variance analysis was continued with further test of honestly significance diffirence (HSD) at 5% level. The observed parameters were plant height (cm), leaf width (cm), number of leaves (strands), wet economic weight (g) and root volume (cm3). The results show that the dosage of Herbafarm fertilizer in pakcoy did not increase the growth and production of pakcoy. The growing medium rockwoolis better to increase the number of leaves, leaf width, economical wet weight and root volume of pakcoy than the cocopeat and charcoal husk as thegrowing media. The combination of organic fertilizers and some growing mediums does not increase the growth and production of pakcoy. Keywords: Pakcoy, Hidroponik, Herbafarm, Rockwool, Cocopeat,Charcoal Husk